2020
DOI: 10.1111/jcmm.14935
|View full text |Cite
|
Sign up to set email alerts
|

Chicoric acid ameliorate inflammation and oxidative stress in Lipopolysaccharide and d‐galactosamine induced acute liver injury

Abstract: Chicoric acid is polyphenol of natural plant and has a variety of bioactivity. Caused by various kinds of stimulating factors, acute liver injury has high fatality rate. The effect of chicoric acid in acute liver injury induced by Lipopolysaccharide (LPS) and d‐galactosamine (d‐GalN) was investigated in this study. The results showed that CA decreased the aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in serum and reduced the mortality induced by LPS/d‐GalN. CA can restrain mitogen‐activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Oxidative stress is established in either acute or chronic liver injury model both in vitro and in vivo , and play an important role during the occurrence and development of these pathological process. It was proved useful to attenuate acute liver injury with anti-oxidant system ( Qi et al, 2019 ; Li et al, 2020c ). To investigate the effects of OEA on oxidative stress in acute liver injury, we detected the hepatic MDA levels, SOD activities and GSH-hx activities at 5 h post LPS/D-Gal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress is established in either acute or chronic liver injury model both in vitro and in vivo , and play an important role during the occurrence and development of these pathological process. It was proved useful to attenuate acute liver injury with anti-oxidant system ( Qi et al, 2019 ; Li et al, 2020c ). To investigate the effects of OEA on oxidative stress in acute liver injury, we detected the hepatic MDA levels, SOD activities and GSH-hx activities at 5 h post LPS/D-Gal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in antioxidant activity by exposure to UV-B in basil leaves has already been shown in the literature [ 3 , 11 ]. The different compounds detected in the extracts analyzed in this study, especially caffeic, rosmarinic, and chicorid acids, have been shown to possess remarkable biological and pharmacological activities both in vitro and in vivo [ 45 , 46 , 47 ], including a high antioxidant capacity. Consequently, the increase in these compounds in basil leaves may enhance their nutraceutical value.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products which can efficiently attenuate oxidative stress and inflammation may be of potential benefit to clinically control and evade ALI [8]. Bioflavonoids can exert bioactive and beneficial effects against metabolic diseases [9].…”
Section: Introductionmentioning
confidence: 99%